Current Challenges in Climate and Weather Research and Future Directions. Issue 3 (8th August 2022) - Lin, Jialin; Qian, Taotao; Bluestein, Howard B.; Ditlevsen, Peter; Lin, Hai; Seiki, Tatsuya; Tochimoto, Eigo; Barnes, Hannah; Bechtold, Peter; Carr, Frederick H.; Freitas, Saulo R.; Goodman, Steven J.; et al.
ABSTRACT: This paper summarizes the current challenges in climate and weather research and provides suggestions for future research directions in global observing systems, in modelling and prediction, and in academic environment and education systems.